Effect of metrics on A based algorithms performance - Volna, Eva (AIP conference proceedings, 2018)
The subject of the paper is to analyze the possibilities of A* based algorithms performance regarding to the metric used to calculate the distances between two objects. The following algorithms have been selected: A*, IDA* (Iterative-Deepening A*) a SMA* (Simplified Memory-Bounded A*). Experimentally, the ability of these algorithms was studied considering to find the shortest path to the target, their ability to deal effectively with obstacles and two tests were focused on testing the load and its influence on the algorithm run. Each of the tests was also aimed at comparing the influence of Euclidean and Manhattan distances, the selection of which in some cases had a major impact on the effectiveness of the algorithm. All achieved results were summarized in the conclusion.